NEGENTROPIC PRINCIPLES OF INFORMATION IN GEOPHYSICS - Бахова, Н. (Proceedings of National Aviation University (archive), 2012)
The ecological functions of the lithosphere are considered. The features of the influence of geophysical fields of lithosphere of natural and anthropogenic origin on the biosphere and human health are analyzed. The fundamental problem of negative entropy decrease required for the life of all living organisms on the Earth is illuminated. The task of studying features of informational interaction of the geological environment and biota was done. The connection between physical entropy and information is studied. The possibilities and difficulties of applying the basic theory of information to the Earth sciences are shown. The information model of a closed living system and rules for data protection at the cellular level have been proposed